Vitamin D/CD46 Crosstalk in Human T Cells in Multiple Sclerosis - Killick, Justin; Hay, Joanne; Morandi, Elena; Vermeren, Sonja; Kari, Saniya; Angles, Thibault; Williams, Anna; Damoiseaux, Jan; Astier, Anne L. (Frontiers in Immunology, 2020)
Multiple Sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS), in which T-cell migration into the CNS is key for pathogenesis. Patients with MS exhibit impaired regulatory T cell populations, and both Foxp3+ Tregs and type I regulatory T cells (Tr1) are dysfunctional. MS is a multifactorial disease and vitamin D deficiency is associated with disease. Herein, we examined the impact of 1,25(OH)2D3 on CD4+ T cells coactivated by either CD28 to induce polyclonal activation or by the complement regulator CD46 to promote Tr1 differentiation. Addition of 1,25(OH)2D3 led to a differential expression of adhesion molecules on CD28- and CD46-costimulated T cells isolated from both healthy donors or from patients with MS. 1,25(OH)2D3 favored Tr1 motility though a Vitamin D-CD46 crosstalk highlighted by increased VDR expression as well as increased CYP24A1 and miR-9 in CD46-costimulated T cells. Furthermore, analysis of CD46 expression on T cells from a cohort of patients with MS supplemented by vitamin D showed a negative correlation with the levels of circulating vitamin D. Moreover, t-SNE analysis allowed the identification of clusters increased by vitamin D supplementation, but not by placebo, that exhibited similar adhesion phenotype to what was observed in vitro. Overall, our data show a crosstalk between vitamin D and CD46 that allows a preferential effect of Vitamin D on Tr1 cells, providing novel key insights into the role of an important modifiable environmental factor in MS.